Effects of liberalization towards haulage industries in Malaysia / Mohd Farez Mat Wahi - Mat Wahi, Mohd Farez (Faculty of Business and Management, 2012)
Container haulage industry plays an important role in the growth of the nation's economy as implementation of liberalization expected will encourage competitiveness among industry players and also to overcome the congestion in port of container movement that labeled by other county as not efficient. This paper discusses various effects of liberalization in many angles. This paper examines the rationale and implications of liberalizing the industry. This paper also investigates the most preferred effect by the various workers that already in the industry by distributing questionnaires to gain their opinion on the effect of liberalization. The researcher found that the most significant effects are liberalization reduce congestion at the port, the other effect is greater number of new entrants and lastly existing company suffer the effects.